Computational genes: a tool for molecular diagnosis and therapy of aberrant mutational phenotype - Ignatova Zoya; Zhang Gong; Martínez-Pérez Israel M; Zimmermann Karl-Heinz (BMC Bioinformatics, 2007)
Abstract Background A finite state machine manipulating information-carrying DNA strands can be used to perform autonomous molecular-scale computations at the cellular level. Results We propose a new finite state machine able to detect and correct aberrant molecular phenotype given by mutated genetic transcripts. The aberrant mutations trigger a cascade reaction: specific molecular markers as input are released and induce a spontaneous self-assembly of a wild type protein or peptide, while the mutational disease phenotype is silenced. We experimentally demostrated in in vitro translation system that a viable protein can be autonomously assembled. Conclusion Our work demostrates the basic principles of computational genes and particularly, their potential to detect mutations, and as a response thereafter administer an output that suppresses the aberrant disease phenotype and/or restores the lost physiological function.